Navigating the maze: ethics approval pathways for intellectual disability research - Thomson, Allyson; Roberts, Peter; Bittles, A (jme bmj, 2013)
All researchers, regardless of their discipline, need to be aware of the importance of protecting vulnerable populations, such as people with intellectual disabilities (ID), from exploitation within the context of research.1 ,2 For this reason, institutional Human Research Ethics Committees (HREC) are regarded as an essential gateway for review of the design and procedure of research projects involving people with ID. While these protections are welcome and necessary, it has been mooted that rigorous application of guidelines of ethical conduct may have a deleterious effect on ID research in Australia.3 One of the common themes identified by a recent review of the ethical aspects of ID research was the importance of participation, notwithstanding an often reduced capacity for autonomous decision making ‘…that neither the presence of a disability nor the absence of capacity should exclude an individual from participation and that the participation of adults with ID in all research should be pursued.’4This paper reviews practical issues arising from a study involving people with ID in Western Australia, and highlights challenges encountered in seeking approval to survey family carers of a group of people with ID. The prescribed involvement of multiple agencies, which was complicated by legislative ambiguities regarding adults who lack the capacity to provide consent for non-medical research participation, resulted in a time span of over 2 years from submission of the initial application to a University HREC to receipt of the final approval for all parts of a project with an original 3-year schedule. The study itself aimed to assess stress levels and explore the use of coping strategies among the carers of people with Angelman syndrome (AS) or Prader–Willi syndrome (PWS). Both syndromes are genomic imprinting disorders that arise from disruptions within human chromosome 15q11-q13. Although the disease phenotypes of the disorders …